2017
DOI: 10.1177/1010428317713492
|View full text |Cite
|
Sign up to set email alerts
|

PPFIA1 is upregulated in liver metastasis of breast cancer and is a potential poor prognostic indicator of metastatic relapse

Abstract: Although the oncogenic role of PPFIA1 (liprin-α1) in breast cancer has been reported, whether its dysregulation is associated with metastasis risk or survival outcomes in breast cancer patients is not clear. Our primary data showed that PPFIA1 expression was significantly higher in liver metastatic breast tumors than in the primary tumors. Then, we tried to pool previous annotated genomic data to assess the prognostic value of PPFIA1 in distant metastasis-free survival, the risk of metastatic relapse, and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
(40 reference statements)
1
12
0
1
Order By: Relevance
“…However, our finding confirmed an oncogenic role of PPFIA1 in tumour cell invasion where we found high PPFIA1 levels is significantly correlated with the development of distant metastasis in the liver. This result ties well with previous study, which showed PPFIA1 expression was significantly higher in liver metastatic tumours than in the primary tumours [24], and PPFIA1 overexpression enhanced cell spreading and cell migration [7]. Altogether, these findings suggesting a potential role for PPFIA1 expression in the invasive process within breast tumour cells.…”
Section: Discussionsupporting
confidence: 93%
“…However, our finding confirmed an oncogenic role of PPFIA1 in tumour cell invasion where we found high PPFIA1 levels is significantly correlated with the development of distant metastasis in the liver. This result ties well with previous study, which showed PPFIA1 expression was significantly higher in liver metastatic tumours than in the primary tumours [24], and PPFIA1 overexpression enhanced cell spreading and cell migration [7]. Altogether, these findings suggesting a potential role for PPFIA1 expression in the invasive process within breast tumour cells.…”
Section: Discussionsupporting
confidence: 93%
“… 125 PPFIA1 (liprin-α1) expression can be significantly higher in the liver metastases than the primary tumors and serves as a potential poor prognostic indicator of increased metastatic relapse in ER + /N − (nodal negative) breast cancer group. 136 β-catenin-independent WNT signaling coincides with a poor prognosis in patients with breast cancer liver metastasis. 124 …”
Section: Liver Metastasismentioning
confidence: 99%
“…A study by Yang et al showed that the gene PPFIA1 is upregulated in those patients with liver metastases and is likely a poor prognostic factor for metastatic growth. 59 This report suggests potential for further research into this and other related genes that may drive metastatic growth within the liver. Additionally, determining whether survival postlocal therapy is associated with PPFIA1 mutation would possibly help in determining which patients are best for locoregional therapies.…”
Section: Breast Cancermentioning
confidence: 87%